2007
DOI: 10.1109/jmems.2007.892909
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Micromachined Titanium Microneedles

Abstract: Microneedle-based drug delivery has shown considerable promise for enabling painless transdermal and hypodermal delivery of conventional and novel therapies. However, this promise has yet to be fully realized due in large part to the limitations imposed by the micromechanical properties of the material systems being used. In this paper, we demonstrate titanium-based microneedle devices developed to address these limitations. Microneedle arrays with in-plane orientation are fabricated using recently developed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 29 publications
3
55
0
Order By: Relevance
“…The insertion force of microneedles depends on microneedles spacing (Parker et al, 2007). This accords well where the insertion force of microneedles depends on microneedles spacing as well as microneedle length .…”
Section: Effects Of Microneedle Spacingsupporting
confidence: 77%
“…The insertion force of microneedles depends on microneedles spacing (Parker et al, 2007). This accords well where the insertion force of microneedles depends on microneedles spacing as well as microneedle length .…”
Section: Effects Of Microneedle Spacingsupporting
confidence: 77%
“…MN have been produced in various geometries. These microstructure geometries can be in the form of needle-like (most common MN geometries which can be sharp-, tapered-, conical-or bevel-tipped), microblades, and blunt-projections or shaped in an arrow-head [47][48][49][50][51].…”
Section: Microneedlesmentioning
confidence: 99%
“…MN have been produced in various geometries. These microstructure geometries can be in the form of needle-like (most common MN geometries which can be sharp-, tapered-, conical-or bevel-tipped), microblades, and blunt-projections or shaped in an arrow-head [47][48][49][50][51].In addition, MNs as a parenteral route of administration could provide the relatively easy and patient-friendly administration of therapeutics with potential efficacy at low cost. And some studies have shown that MNs can penetrate the skin, cross the stratum corneum into the viable epidermis, and reside primarily in the dermal layer, avoiding contact with blood vessels and nerve fibres.…”
mentioning
confidence: 99%
“…The most common materials used for fabricating MN are metal, silicon and polymer (Zhao et al, 2006;Memon et al, 2011;Kim et al, 2012). The primary metals used for MNs are stainless steel (Martanto et al, 2004;Bal et al, 2008;Quan et al, 2010;Kim et al, 2012) and titanium (Parker et al, 2007;Fernandez et al, 2009;Kim et al, 2010). Metal MNs have the advantages of low cost, tougher hardness, ease of penetration into the tissue and they are not easily broken in the tissue.…”
Section: Gas Pressure and Particle Velocitymentioning
confidence: 99%